Prevalence of platinum-induced ototoxicity among patients suffering from hematological malignancies – a systematic review - Janowiak-Majeranowska, Aleksandra; Abdulaziz-Opiela, Gazala; Osowski, Jakub; Mikaszewski, Bogusław (Contemporary Oncology/Współczesna Onkologia, 2024)
Platinum-based compounds used for treating hematologic malignancies can lead to various side effects. One such side effect is ototoxicity, which is characterized by permanent bilateral sensorineural hearing loss or tinnitus. Initially, it mainly affects high frequencies, but as the condition progresses, it may also affect low frequencies. Occurrence of ototoxicity has been reported in up to 80% of patients. However, the precise incidence among hematology patients remains unknown. Following Preferred Reporting Items for Systematic Reviews and meta- analyses guidelines, a systematic review was conducted to assess the incidence of ototoxicity among hematology patients undergoing platinum compound-based chemotherapy. Four databases – PubMed, Scopus, Embase, and Web of Science – were searched to identify relevant articles published in the period 2000–2023. Initially, 538 articles were screened, with only 5 meeting the criteria for inclusion in the analysis. The systematic review included a total of 77 patients, the majority of whom had Hodgkin’s lymphoma (65 patients, 84.4%). Only one patient had leukemia. Of all patients, 16 (20.8%) developed ototoxicity. It is crucial for hematologic patients to undergo regular monitoring and audiometric tests even up to 10 years after treatment. Conducting prospective studies to evaluate hearing before, during, and after treatment is necessary to enhance the management of hematological patients.